PENGUKURAN EFISIENSI DAN EFEKTIVITAS PENGELOLAAN KEUANGAN DAERAH PADA BADAN PENDAPATAN DAERAH KABUPATEN SUMBAWA TAHUN 2018-2021 - Novida Halleine Putri; Jayanti Mandasari; Diah Intan Syahfitri (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
This research aims to determine the level of efficiency and effectiveness of regional financial management at the Sumbawa Regency Regional Revenue Agency (BAPENDA) in 2018-2021. The method used in this research is qualitative. The informant in this research was the secretary of BAPENDA. The data collection method used is field study (observation), where after obtaining the data it is then calculated using the efficiency ratio and effectiveness ratio formula, interviews and documentation. The results of measuring the efficiency ratio show that the level of efficiency in regional financial management of the Sumbawa Regency government in 4 years has fluctuated with an average level of efficiency of 69.03% with the Efficient category, The results of measuring the effectiveness ratio show that the effectiveness level of regional financial management of the Sumbawa Regency government in 4 years has fluctuated with an average level of effectiveness of 95.69% with the Effective category, This shows that the government's performance in realizing regional income based on real regional potential in the 2018 - 2021 budget year has been very good. Based on the research results, it can be described that the regional financial management of Sumbawa Regency is still unstable. This is caused by the Regency regional government. Keywords: Efficiency, Effectiveness, Regional Financial Management, Regional Income